2012
DOI: 10.1088/1742-6596/345/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the kidney, liver and spleen during prolonged administration of iron nanoparticles

Abstract: Abstract. We determined the cytotoxic effect of iron nanoparticles of 70 nm, with a single per oral administration in an experiment on white outbred mice. Morphological changes were evaluated in the internal organs. Thus, changes depend on the concentration of nanoparticles at long-term per oral exposure: identified violations of the structure of the liver, kidneys and spleen as venous plethora and degeneration of cells at 250 and 500 mkg / kg dose of nanoparticles are reversible, changes in the organs were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Clinical trials have shown excellent biocompatibility of magnetite nanoparticles [16][17][18]. Low toxicity was also determined in vivo by morphological study of internal organs of laboratory animals after different methods of administration of magnetite nanoparticles [19][20][21].…”
Section: Overviewmentioning
confidence: 99%
“…Clinical trials have shown excellent biocompatibility of magnetite nanoparticles [16][17][18]. Low toxicity was also determined in vivo by morphological study of internal organs of laboratory animals after different methods of administration of magnetite nanoparticles [19][20][21].…”
Section: Overviewmentioning
confidence: 99%
“…Magnetite is quite a promising material for biomedical applications, in different studies indicates that such nanoparticles have low toxicity, good biocompatibility and sufficient magnitude of effective magnetic characteristics [10,11]. Low toxicity was also confirmed by vivo studies and morphological examination of internal organs of animals after different methods of administration of magnetite nanoparticles [12][13][14].…”
mentioning
confidence: 99%